Pyridoxine Refractory Sideroblastic Anemia: Diagnosis and Misdiagnosis - Muhammad Matloob Alam; Abdulrhman Alathaibi; Ruwayd Adel Attar; Muhammad Kashif; Hamdan Saeed Al-Ghamdi; Sultan Abdulaziz Alharthi; Abdulmohsen Bokhary; Muteb Althomali (The Korean Society of Pediatric Hematology-Oncology, 2022)
We report the case of a 7-year-old girl who was originally diagnosed at the age of 6 months with transfusion-dependent red cell aplasia based on a combination of severe anemia, reticulocytopenia and bone marrow findings. Since early infancy due to severe microcytic/hypochromic anemia she received multiple packed RBCs transfusions. She subsequently developed hepatomegaly, hypothyroidism, diabetes, liver cirrhosis and latterly, a severe cardiomyopathy due to significant iron overload refractory to regular chelating agents. Genetic study was offered, confirmed the presence of SLC25A38 gene mutation and her diagnosis was revised to pyridoxine refractory sideroblastic anemia (PRSA). It is a non-syndromic, autosomal recessive disorder, characterized by severe microcytic anemia since infancy and increased serum ferritin, which is not responsive to pyridoxine. Since the clinical course of this disorder is very similar to that of thalassemia major and other red cell aplasia. Prompt recognition and initiation of appropriate treatment are important to reduce the development of secondary disease complications due to iron overload. Given the potential for misdiagnosis and delay in the recognition of sideroblastic anemia, a careful bone marrow examination and genetic study should be included while investigating children with unexplained anemia.